608 Efficacy of a Treatment for Sleep-Related Problems in Children with Anxiety: A Mixed Methods Study. (3rd May 2021) - Chevalier, Lydia; Pariseau, Emily; Long, Kristin; Langer, David; Pincus, Donna
Abstract: Introduction: School-aged children with anxiety frequently experience sleep-related problems (SRPs) such as bedtime resistance. Results are mixed, but some children with anxiety also report longer sleep onset latency (SOL). Despite the link between SRPs and mental and physical health consequences, limited research has evaluated the efficacy of brief sleep treatments in this population. Methods: A mixed methods approach employing a multiple-baseline single-case design and qualitative methods was used to evaluate the efficacy of a four-session parent training intervention in ten children with anxiety and chronic insomnia (M=9.6 years, range 8–12 years, 8 female). Questionnaires on SRPs and anxiety were completed by parents and children at baseline, one-week post-treatment, and one-month follow-up assessments. Subjective SOL (i.e., sleep diary) and objective SOL (i.e., actigraphy) were measured daily during assessment and treatment weeks. Parents and children completed qualitative interviews at the post-treatment assessment. Results: The majority of participants no longer met criteria for chronic insomnia at post-treatment (n=9) or follow-up (n=6). SRPs (e.g., bedtime resistance) were significantly less frequent at post-treatment and follow-up than at baseline. The majority of participants demonstrated significant reductions in subjective (n=7) but not objective (n=3) SOL at post-treatment or follow-up compared to baseline. Qualitatively, parents and children described improvements in sleep during treatment. Some parents described discovering while completing sleep diaries that their child believed themselves to be taking longer to fall asleep at the beginning of treatment than they actually were (i.e., sleep misperception), and that this sleep misperception improved during treatment. Conclusion: The findings of the current study support the preliminary efficacy of a brief parent training intervention to treat SRPs in school-aged children with anxiety. They also begin to help elucidate mixed findings in the literature on sleep of children with anxiety by providing a potential reason for discrepancies between subjective and objective SOL in this population. Specifically, qualitative findings suggest that this discrepancy may be related to sleep misperception, that children with anxiety may feel themselves to be taking a long time to fall asleep even when objective measures of SOL are within the normative range. Support (if any): Boston University Clara Mayo Memorial Research Fellowship